Financial Performance and Firm Value: The Role of Signaling Theory - Putri, Indah Ayu Johanda; Budiyanto; Triyonowati, (International Journal of Scientific Research and Management (IJSRM), 2023)
The purpose of this study is to analyze and explain empirical evidence in the automotive industry about the effect of company size, company growth, and intellectual capital on financial performance and company value. The approach used in this research is quantitative. The results showed that company size, company growth, and intellectual capital have an effect on financial performance. Firm size and intellectual capital, and financial performance have a significant effect on firm value. While the company's growth has no significant effect on firm value. Judging from the indirect effect, financial performance mediates the influence of company size, company growth and intellectual capital on firm value. Future research can also conduct further research on automotive companies using the same variables and in measuring company size and company growth can add indicators and also use primary data by conducting interviews with the company, so that the results of measuring company size and company growth are more comprehensive.